2023
DOI: 10.1088/2631-8695/acbfa1
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of scour around various shaped bridge pier

Abstract: The study of scouring around bridge piers is very significant and plays a very important role in the safe and economical design of bridge piers. The term scouring is a process by which bed particles around the periphery of the pier get eroded and removed over a certain depth resulting in the formation of a scour hole around the bridge piers. This paper presents a detailed investigation of local scouring around six different shapes namely rectangular, circular, chamfered, joukowsky, oblong, and sharp-nosed of b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 45 publications
(42 reference statements)
0
5
0
Order By: Relevance
“…The interaction between these two vortices creates a complex flow pattern that contributes to the scouring process. The horseshoe vortex generates a high-velocity jet of water along the face of the pier, leading to concentrated erosion at the base of the pier (Baranwal et al 2023b). Furthermore, the wake vortex generates a low-pressure zone downstream of the pier, causing sediment to be transported away from the riverbed.…”
Section: Mechanism Of Scouring Around Bridge Piersmentioning
confidence: 99%
“…The interaction between these two vortices creates a complex flow pattern that contributes to the scouring process. The horseshoe vortex generates a high-velocity jet of water along the face of the pier, leading to concentrated erosion at the base of the pier (Baranwal et al 2023b). Furthermore, the wake vortex generates a low-pressure zone downstream of the pier, causing sediment to be transported away from the riverbed.…”
Section: Mechanism Of Scouring Around Bridge Piersmentioning
confidence: 99%
“…al. [67] Keshavarzi et al [68] Garg et al [69] Mohsen [70] Mohsen et al [71] Tafarojnoruz et al [45] Li et al [72] Deflector scheme Odgaard et al [73] Chauhan et al [74] Ghorbani et al [57] Zarei et al [75] Safaripor et al [76] Sand barrier scheme Guan et al [77] Hamidifar et al [78] Mahdi et al [79] Grimaldi et al [80] Liang et al [44] Tafarojnoruz et al [45] AI-Awadi et al [81] Pagliara et al [82] Gaudio et al [47] Pile alteration scheme AI-Shukur [83] Farooq et al [84] Baranwal et al [85] Aly et al [11] Informed Consent Statement: Not applicable.…”
Section: Conflicts Of Interestmentioning
confidence: 99%
“…Scouring depth around bridge piers depends on the intensity of approach flow, sediment transportation, and geometrical features of bridge piers. When horseshoe vortices form at the base of the pier, they cause erosion [1,2]. The degree of scouring is a crucial component that contributes to the collapse of the bridge base.…”
Section: Introductionmentioning
confidence: 99%
“…This interference resulted in local scour. Researchers such as [4][5][6] have conducted research over the past several decades and reported that the most common reason for bridge collapse is the removal of bed materials from the stream bed in the area close to the pier or abutment foundation. It is found that scouring around bridge piers is one of the main factors contributing to bridge deterioration.…”
Section: Introductionmentioning
confidence: 99%